2019
DOI: 10.1155/2019/2527384
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Impairment after Minor Stroke and Non-ST-Elevation Myocardial Infarction (NSTEMI): A Prevalence Study

Abstract: Aim. To study the prevalence of cognitive and emotional impairment following a minor ischemic stroke compared to an age-matched group with non-ST-elevation myocardial infarction (NSTEMI). Methods. We included patients aged 18-70 years with a minor ischemic stroke defined as modified Rankin Scale (mRS) 0-2 at day 7 or at discharge if before and age-matched NSTEMI patients with the same functional mRS. We applied a selection of cognitive tests and the patients completed a questionnaire comprising of Hospital Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
6
1
Order By: Relevance
“…Examining the association between psychiatric symptoms and performance-based function, we found that higher levels of anxiety and phobic anxiety were associated with poorer cognitive function. This differs from earlier work, which did not find a relation between anxiety and cognition 12 months after a minor stroke (Morsund et al, 2019). Inconsistent results might be due to the time of assessment, as anxiety is less prevalent 6-12 months post-stroke compared to the first 6 months (Knapp et al, 2020).…”
Section: Subsample Analyses I: Psychiatric Symptoms and Performance-bcontrasting
confidence: 99%
See 2 more Smart Citations
“…Examining the association between psychiatric symptoms and performance-based function, we found that higher levels of anxiety and phobic anxiety were associated with poorer cognitive function. This differs from earlier work, which did not find a relation between anxiety and cognition 12 months after a minor stroke (Morsund et al, 2019). Inconsistent results might be due to the time of assessment, as anxiety is less prevalent 6-12 months post-stroke compared to the first 6 months (Knapp et al, 2020).…”
Section: Subsample Analyses I: Psychiatric Symptoms and Performance-bcontrasting
confidence: 99%
“…Higher levels of depressive symptoms were associated with lower performance-based memory but not with attention/ executive function. Cognitive impairments and depression are highly prevalent after minor stroke (Moran et al, 2014), and several studies have found an association between symptoms of depression and cognitive domains such as verbal memory, cognitive speed (Barker-Collo, 2007), and executive function (Morsund et al, 2019). Our study extends these findings to patients with good outcomes after stroke.…”
Section: Psychiatric Symptoms and Cognition After Strokesupporting
confidence: 75%
See 1 more Smart Citation
“…Lacking a stroke-free control group, we were unable to evaluate whether cognition is more severely impaired in those who have suffered a stroke than in the background population. A recent study found no differences in cognitive function between patients with minor stroke and those with myocardial infarction 1 year after the vascular event ( 36 ). Additionally, in our study population comprising both first-ever and recurrent strokes, an evaluation of the effects of recurrent strokes is limited.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,47 Greater stroke severity has also been associated with increased risk of PSD, though this relationship may be mediated by degree of disability. 8,47 Cognitive impairment appears to be a risk factor for PSD, 8,47,53,54 with greater executive dysfunction associated with worse depression outcomes. 55 A proposed association between lesion location, laterality, and PSD has been the subject of extensive debate, with early studies by Robinson and colleagues suggesting a link between left hemisphere (especially left frontal) lesions and subsequent depression.…”
Section: Demographic Variablesmentioning
confidence: 99%